1998
DOI: 10.1074/jbc.273.5.2844
|View full text |Cite
|
Sign up to set email alerts
|

The Three-dimensional Structure of Cys-47-modified Mouse Liver Glutathione S-Transferase P1-1

Abstract: The three-dimensional structure of mouse liver glutathione S-transferase P1-1 carboxymethylated at Cys-47 and its complex with S-(p-nitrobenzyl)glutathione have been determined by x-ray diffraction analysis. The structure of the modified enzyme described here is the first structural report for a P i class glutathione S-transferase with no glutathione, glutathione S-conjugate, or inhibitor bound. It shows that part of the active site area, which includes helix ␣B and helix 3 10 B, is disordered. However, the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Tyr 7 does not appear to play a role as a general base in the enzymatic reaction. Similar conclusions have been reported for other mammalian -class GSTs (19,21,59). …”
Section: Discussionsupporting
confidence: 76%
“…Tyr 7 does not appear to play a role as a general base in the enzymatic reaction. Similar conclusions have been reported for other mammalian -class GSTs (19,21,59). …”
Section: Discussionsupporting
confidence: 76%
“…B zone is stabilized upon binding of the substrates, as observed in the structure of the unliganded Cys-47-carboxymethylated mGST P1-1 enzyme, where the absolutely disordered helices αB and 3 "! B are partially organized upon binding of S-(p-nitrobenzyl)glutathione [30]. We observe also that the binding of a hydrophobic substrate in the form of a GSH adduct [12] increases the definition of the electron density, and decreases the atomic B-factors (although they are still higher than the rest of the protein), in comparison with mGST P1-1:GSH.…”
Section: Helices αB and 3 10 B Show Higher Mobility In The Absence Ofmentioning
confidence: 93%
“…ez and co-workers [12] suggested that, should Tyr-7 be in its ionized form, a positively charged residue could be in closer proximity in the free enzyme and be removed when GSH binds. The structure of the unliganded Cys-47-modified enzyme [30] proves that this is not the case (see below). Other observations [9,31,32] also argue against the tyrosinate hypothesis, and other functional groups of the protein [33] or even the carboxyl groups of GSH [34] have been proposed as the proton acceptors.…”
Section: Figure 1 Ribbon Representation Of One Monomer Of the Mgst P1mentioning
confidence: 94%
See 1 more Smart Citation
“…It is easily expressed in E. coli and well characterized. 14, 15 This relatively small protein features four cysteine residues (Cys-14, 47, 101 and 169), among which Cys-47 has the highest reactivity due to its relatively low pKa (3.5–4.2) and accessibility. 16 …”
mentioning
confidence: 99%